The Readiness for Integrated Primary Health Care (ILP) at Puskesmas Pamulang in Tangerang Selatan City - Rachmaningsih, Firda Safitri; Sari, Kurnia (Journal of Indonesian Health Policy and Administration, 2025)
. Integrated primary healthcare (ILP) is part of the transformation of primary healthcare aimed at improving access to quality healthcare. This study aims to analyze the readiness of Pusat Kesehatan Masyarakat (Puskesmas) and their networks to implement ILP. This research used a qualitative approach, focusing on a case study of a Puskesmas in an urban setting, specifically in the operational area of Puskesmas Pamulang in South Tangerang. Data collection methods include in-depth interviews, observations, and document reviews. This research adopts the conceptual framework of PHC monitoring based on WHO and Weiner's theory of organizational change readiness. The research findings indicate that ILP readiness at Puskesmas is not fully prepared for cluster-based services, networking approaches, and digitalization strengthening. Resource availability, including human resources, infrastructure, and facilities, is inadequate, particularly at the Puskesmas network level. Readiness for digital technology is constrained and the lack of funding hampers ILP preparation. Individual commitment, demonstrated through understanding information and positive assessments of ILP, and organizational commitment evidenced by governance support and allocated funding, are factors facilitating ILP implementation. The study recommends prompt funding allocation for ILP preparation, resource fulfilment at Puskesmas and Pos Pelayanan Terpadu (posyandu), and the need for cooperation and commitment from all stakeholders in ILP implementation.